PENENTUAN KEPUTUSAN INVESTASI SAHAM BERDASARKAN UNDERVALUED ATAU OVERVALUED DENGAN PENERAPAN CAPM - Kennedy, Posma Sariguna Johnson; Yanis, A (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2019)
This study aims to help investors in determining stock investment decisions by applying the CAPM method in determining stocks classified undervalued or overvalued based on the level of risk and the rate of return. This research uses quantitative descriptive approach method. The result of this research shows that from the stock of 15 companies of plantation sub sector which become the sample of research, there are seven stocks of companies classified as undervalued ie ANJT, BWPT, DSNG, LSIP, SGRO, SIMP, TBLA shares with investment decision ie buying shares and eight companies classified overvalued ie AALI, GZCO, JAVA, MAGP, PALM, SMAR, SSMS, UNSP, with the investment decision that is selling shares. Keywords: CAPM, systematic risk, rate of return, undervalued, overvalued.